Pengaruh Capital Intensity, Umur Perusahaan, Komite Audit, dan Board Gender Diversity Terhadap Tax Avoidance - Tegar Prasetyo; Alexander Raphael (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
The purpose of this research is to empirically examine the effect of capital intensity, firm age, audit committee and board gender diversity on tax avoidance. Tax avoidance in this study was measured using the Effective Tax Rate (ETR). This research is a quantitative research and uses sector energy sub sector mining companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period as research objects. The sample selection technique used purposive sampling with a total of 40 samples obtained from 8 sector energy sub sector mining companies. Hypothesis testing in this study was carried out using E-views software version 16. Based on the results of the hypothesis testing that had been carried out, it can be concluded that 1) capital intensity has effect on tax avoidance; 2) firm age has no effect on tax avoidance; 3) the audit committee has no effect on tax avoidance, 4) board gender diversity has no effect on tax avoidance.